Inferring transpiration control from sap flow heat gauges and the Penman-Monteith equation - Aiken, Robert M.; Klocke, N. L. (My University, 2012)
In situ measurements of crop transpiration can enhance field studies of crop water use and productivity. Our objectives were to develop and evaluate a canopy resistance model, to evaluate operational characteristics of sap flow heat gauges (SFHG) for field corn (Zea mays L.), and to compare transpiration flux calculated by SFHG with evapotranspiration (ET) calculated by a Penman-Monteith (P-M) algorithm. Five sap flow heat gauges, controlled by an automated data acquisition system, were deployed in each of four replicated field plots of corn irrigated to limit water deficits to 50% of available water capacity at Garden City, Kansas, in 2004 and 2006. Water flux through each stem was estimated as a residual of a heat balance equation. Gauges were transferred to adjacent plants after 13 to 21 days to evaluate and mitigate functional stem damage. Loss of gauge operation, primarily due to stem damage, commonly occurred approximately one to two weeks following installation. Data screened using operational metrics were used to evaluate a scaling relationship between calculated flow to ET calculated following the P-M form. A canopy resistance model was derived from principles of radiation use. Transpiration calculated from gauge data was linearly related to ET calculated from the P-M, with R[superscript]2 exceeding 0.79. Greater precision was obtained by assuming constant canopy resistance (r[subscript]c), but predictive bias was reduced by assuming that r[subscript]c was proportional to solar radiation. Sap flow gauges provided information useful for calibrating an r[subscript]c model for P-M to calculate the transpiration component of ET; the model linking canopy resistance to absorbed radiation has application to dual-source and thermal-based energy balance models of crop ET.
Keywords: Canopy resistance; Evaporation; Penman-Monteith; Radiation use; Sap flow heat gauges; Transpiration